Impact of SARS-CoV-2 Treatment on Development of Sensorineural Hearing Loss: Impact of SARS-CoV-2 treatment on SNHL - Ghulam, Tahira; Rafi, Hira; Khan, Asra; Gul, Khitab; Z. Yusuf, Muhammad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Ototoxicity had been a known viral manifestation. This raised the possibility for the current pandemic caused by the novel coronavirus to induce temporary or permanent auditory manifestations. The struggle to search for therapeutic options to counter the pandemic is still underway. Meanwhile, the management had relied on using antimalarials and antivirals; which themselves have proven ototoxic repercussions. Interestingly this brings to a point of further debate whether the auditory dysfunction is induced by the virus alone or by the drugs that are used to pacify the pathology of the viral exhibition or both. This article will channel this current implication of the hearing loss debate focusing on the mainstay regimen for SARS-CoV-2 management. A bibliographic search was performed to review current literature in scientific databases PubMed, Research Gate, and Google Scholar. Published articles encompassed within our inclusion criteria were reviewed thoroughly to draw possible outcomes. Reported SARSCoV-2 manifestations are sensorineural hearing loss with disturbed vestibulo-auditory symptoms. Reviewed research data suggested aggravation in ototoxicity induced by these medications. This upsurges the controversies surrounding the safety and efficacy of the medications currently in active use for managing SARS-CoV-2 infection. Further therapeutic strategies need to be researched for equipping the arsenal to effectively treating SARS-CoV-2 and its complications.